Clinical Oral Medicine and Pathology - Bruch, Jean M.; Treister, Nathaniel (Springer International Publishing : Imprint: Springer, 2017)
Following on the favorable reception of the first edition, the authors have thoroughly revised and updated the second edition of this resourceful clinical handbook. The book has been well received internationally by a wide audience of clinicians, including general dentists, oral surgeons, otolaryngologists, primary care physicians, nurse practitioners, dental hygienists, physician assistants, and dermatologists, and sales have been strong among students and post-graduate residents training in medical, dental, and allied health fields, supporting the versatility of this work and serving as testimony to its value in both the academic and private practice arenas. Several key updates and improvements have been made to the second edition. All informational content has been updated to ensure accuracy and relevance, particularly in the rapidly evolving fields of oncology and pharmacology. A new chapter has been added entitled "Oral Sequelae of Cancer and Cancer Therapy" which better organizes and consolidates previous content while expanding on topics such as targeted therapies and hematopoietic stem cell transplantation. Additional clinical images have been included throughout the book so that the full clinical spectrum of any given condition is well-represented. Furthermore, the print quality, as well as the positioning and layout of the clinical images has been improved for optimal utility. Lastly, the summary boxes that follow each condition have been reconfigured with color-coded icons for improved definition, ease of use and cross-referencing. Clinical Oral Medicine and Pathology, Second Edition will continue to serve as an authoritative contemporary resource for clinicians seeking guidance in the diagnosis and management of oral diseases.
Keywords: Medicine.; Otorhinolaryngology.; Pathology.; Oral surgery.; Maxillofacial surgery.; Surgical oncology.; elektronické knihy; electronic books